Can we reform the welfare in times of grey majorities? The myth of an electoral opposition between younger and older voters in Germany - Achim Goerres (Max Planck Institute for the Study of Societies, 2007)
Is there an antagonism between young and old in the electoral arena that could lead to the obstruction of welfare-state reforms? This article argues that this notion is a myth and lacks empirical evidence for the case of Germany. It is true that (a) there are imminent majorities of voters aged 50 and older; (b) older voters benefit from many welfare state programs and (c) life-cycle interests shape some attitudes towards single public policies. However, these facts alone do not represent an antagonism between young and old in the electoral arena. Firstly, differences in party preferences between age groups are due to generational effects associated with early political socialization. Secondly, life-cycle interests do not shape the German party competition because age is not a political division line (cleavage). Young age/old age is only a transitional boundary that all of us aspire to cross, meaning that material old-age interests are important to everyone. Finally, grey interests parties are notoriously weak and try to become parties for the interests of all age groups. – – Gibt es bei Wahlen einen Interessensgegensatz zwischen Jung und Alt, der wohlfahrtsstaatliche Reformen erschweren könnte? Der vorliegende Beitrag entlarvt diese Vorstellung als einen Mythos, für den es im deutschen Fall keine empirische Evidenz gibt. Es ist richtig, (a) dass es in Deutschland bald Mehrheiten von Wählerinnen und Wählern geben wird, die 50 Jahre und älter sind, (b) dass ältere Wähler von vielen wohlfahrtsstaatlichen Programmen profitieren und (c) dass durch den Lebenszyklus gesteuerte Interessen die Einstellungen zu einzelnen Policies formen. Doch diese Ergebnisse stellen noch keinen Gegensatz zwischen Jung und Alt in der Wahlarena dar. Erstens gehen die unterschiedlichen Wahlergebnisse für einzelne Altersgruppen auf Gegensätze zwischen Generationen zurück, die in früher politischer Sozialisation begründet sind. Zweitens beeinflussen die durch den Lebenszyklus definierten Interessen nicht den deutschen Parteienwettbewerb, weil Alter nicht das Potenzial für eine politische Konfliktlinie (cleavage) hat. Die Kategorien Jung und Alt sind nur durch eine durchlässige Grenze voneinander getrennt, die alle Individuen zu überschreiten hoffen. Somit sind auch die materiellen Interessen älterer Menschen für alle wichtig. Drittens sind alle Seniorenparteien schwach und versuchen sich als Parteien aller Altersgruppen neu zu profilieren.
Keywords: 300